2014
DOI: 10.1177/1071100714550651
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Tendons Hypertrophy in Response to High Loading Training

Abstract: Level II, etiology study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
1
18
1
1
Order By: Relevance
“…Previous studies indicated that different degrees of transducer pressure could affect the morphological properties of the AT (Brushoj et al 2006; Dudley-Javoroski et al 2010; Milgrom et al 2014). Milgrom and colleagues (2014) suggested that calculations of the AT hypertrophy are better performed by changes in the CSA rather than thickness. Our results showed that maximal probe pressure could alter (~6%) both AT CSA and thickness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that different degrees of transducer pressure could affect the morphological properties of the AT (Brushoj et al 2006; Dudley-Javoroski et al 2010; Milgrom et al 2014). Milgrom and colleagues (2014) suggested that calculations of the AT hypertrophy are better performed by changes in the CSA rather than thickness. Our results showed that maximal probe pressure could alter (~6%) both AT CSA and thickness.…”
Section: Discussionmentioning
confidence: 99%
“…First, we have to note that we used two different digitization methods for US and MRI image analysis. In the past, several US studies used manual tracing (Brushoj et al 2006; Dudley-Javoroski et al 2010; Intziegianni et al 2015), equation-based digitization (Milgrom et al 2014), or assumptions of the tendon shape (Kallinen and Suominen 1994) to assess the AT CSA. Moreover, MRI images were traced manually (Brushoj et al 2006) or automatically (Hansen et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each participant laid face downwards on a physiotherapy table with their ankle joint in a neutral position. A 46 mm 5-11 MHz linear ultrasound probe (model L745) was placed perpendicularly to the Achilles tendon, between the medial and lateral malleoli [21]. The medial-lateral and anteriorposterior dimensions were recorded, and the crosssectional area was calculated using the associated formula for an oval, i.e., Anterior-posterior * medial-lateral * π/4.…”
Section: Orthosesmentioning
confidence: 99%
“…Olympic weightlifting trainings are known to bring about hypertrophy in lower limb muscles and tendons along with a higher level of stiffness (Kubo et al 2007(Kubo et al , İnce 2019. In addition, athletic activities provide a hypertrophic effect on ATT and cross-sectional area of elder and athletic individuals (Kallinen and Suominen 1994, Emerson et al 2010, Milgrom et al 2014). When we compare ATT measurements of athletes in Olympic weightlifting and sedentary individuals, we might say that long-term physical trainings cause a hypertrophic effect of AT of the athletes.…”
Section: Discussionmentioning
confidence: 99%